An Approach to the Idea of Friendship in the Epistolary of Paulinus of Nola: El enfoque singular de la amistad cristiana en el periodo tardoantiguo - Morales, Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The perspective of friendship in Late Antiquity constitutes a considerable horizon for reflection and analysis. This paper aims to delimit the singular characteristics of friendship in the Christian world of the fourth century A.D. and, more specifically, to delve into the epistolary legacy of Paulinus of Nola, considered one of the great figures of the patristic period, whose postulates reflect a notorious incidence of friendship. To do so, I will first offer an overview of his life; then I will examine the theme of amicitia in his epistolary; finally, I will unravel the notion of epistolary friendship with Augustine of Hippo.